Reply to ’Some More Comments on Folate Deficiency in Chronic Pancreatitis’ - Rajesh, Gopalakrishna; Girish, Banavara Narasimhamurthy; Vaidyanathan, Kannan; Saumya, Menon; Balakrishnan, Vallath (JOP. Journal of the Pancreas, 2010)
No abstract available. Image: Folic acid crystals (Author: W. Oelen; Wikimedia Commons).